Pengaruh Pendidikan Suami Pendidikan Istri dan Pendapatan terhadap Fertilitas di Kelurahan Sungai Kapih Kota Samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
This research aimed at analyzing the significant influence of husbands knowledge, wifes knowledge and income simultaneously on fertility in Sungai Kapih district, Samarinda. It also intended to find the most dominant variable among these variables: husbands knowledge, wifes knowledge and income that influences fertility in Sungai Kapih district, Samarinda. The data were analyzed using multiple regression. The result showed that income positively influenced fertility in Sungai Kapih district, Samarinda. This indicates that the higher peoples level of income, the higher a possibilty of the fertility rate decreases with the purpose of children quality development.Keywords: husbands knowledge wifes knowledge